The Role of English Debating Tournament in the Face of ASEAN Economic Community (AEC) - Husnawadi, Husnawadi; Syamsudarni, Syamsudarni (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Since its establishment in the late 2015, the ASEAN Economic Community (AEC) with English as the official language has forced its participating countries to improve the quality of English language teaching, in the hope to prepare their people to be globally competitive. The lack of English proficiency, however, remains the main challenge across the country members. English forensic or debating tournament has been proven to bring about globally competitive individuals in terms of being highly competent in English together with having higher order thinking skills. Grounded in Indonesian context, this paper presents (1) typology of English debating tournaments in Indonesia, (2) how English debating improves the language competence and critical thinking skills by drawing on some of respective research, (3) An example of its practice in an EFL classroom in Indonesia and its principles, (4) and its implications on the teaching of English in Indonesian.